The Comparative Characteristics of Spontaneous Infection of Ticks in Natural Foci of Bacterial Tick-Borne Infections in Natural Foci in the Western and Eastern Baikal Region - D. O. Kiselev; Yu. P. Dzhioev; I. V. Kozlova; L. A. Stepanenko; A. A. Badmaev; V. I. Zlobin (Эпидемиология и вакцинопрофилактика, 2025)
Relevance. The study of natural foci of infections transmitted by ticks is an integral part of the study of the clinical and epidemiological characteristics of this group of diseases and their manifestations in various endemic areas.The aim of this work was to obtain up-to-date information regarding the spread of the most epidemically significant pathogens of bacterial infections carried by ticks in natural foci of the Baikal region using molecular analysis methods.Materials & Methods. Analyzed infections of I. persulcatus with pathogens transmitted by ticks (Borrelia spp., Ehrlichia spp., Anaplasma spp.) in natural foci in the Baikal region of Russia with determination of the species diversity of Borrelia (B. afzelii, B. garinii, B. miyamotoi) in the studied material. The study used RT-PCR for detection.Results. The total infection of ticks with Borrelia - 45.3%, Ehrlichia - 16.0% and Anaplasma - 15.9%. The study shown the unevenness of infection of ticks by pathogens in the study area. The dominant species of Borrelia was B. garinii - 44.0% of cases, in second place was B. miyamotoi - 15.9%, B. afzelii - 13.6%, Borrelia of unidentified species - 34.0%. The analysis recorded the differences in the infection ticks with B. afzelii, B. garinii and B. miyamotoi between different parts of the Baikal region.Conclusions. The obtained data complement and expand the understanding of the species diversity of natural focal infections carried by ticks in the Baikal region and can be used in further scientific research and in organizing preventive and therapeutic measures in case of infection with the pathogens considered in the study.